Pengembangan Kapasitas UMKM melalui Sosialisasi Literasi Keuangan, Inklusi Keuangan, dan Pelatihan Permodalan di Kecamatan Tatanga dan Kelurahan Nunu - Fadli Hadi Badjeber; Fajria Fajria; Siti Lista Fatimah; Dewi Sangfitri; Safni J. Aziz; Siva Natun; Zazkia Hairunnisa; Dina Adinda (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the regional economy, including in Tatanga District and Nunu Village, Palu City. However, many MSME actors in these areas still face fundamental challenges such as low financial literacy, limited access to capital, and insufficient use of digital technology in business management. These limitations lead to weak financial record-keeping, poor cash flow management, and inadequate readiness to meet bankability requirements when applying for financing from formal financial institutions. This community service program was designed to improve the understanding and practical skills of MSME actors through financial literacy socialization, financial inclusion education, capital training in collaboration with financial institutions, and training in simple financial record preparation. The program was implemented using needs assessments through observation, structured material delivery, interactive discussions, hands-on transaction recording practice, and learning evaluations through pretests and posttests. The results show a significant improvement in participants’ competencies. Average scores for financial literacy and inclusion increased from 48% to 89%, indicating better understanding of cash flow management, transaction recording, and the use of digital financial services such as QRIS and mobile banking. Furthermore, participants’ understanding of capital access improved from 51% to 92%, particularly regarding financing procedures, business eligibility requirements, and the importance of financial statements in loan applications. Overall, the program effectively strengthened MSME capacity to manage businesses in a more structured, adaptive, and professional manner, supporting MSME independence and long-term business sustainability in Tatanga District and Nunu Village.